2014
DOI: 10.1097/nhh.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Pain Assessment and Management Strategies for Elderly Patients

Abstract: Home healthcare nurses play a critical role in pain assessment and management in elderly patients. People 65 years of age and older are the largest consumers of prescription and nonprescription pain medications in the United States and are at increased risk for adverse reactions and inadequate pain management. This article seeks to explore strategies to assist hospice and home healthcare nurses in assessing and managing elderly patients' pain. The goal is to provide tools to assist nurses in streamlining elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The difficulties in identifying and assessing pain, as well as residents' resistance to reporting pain, were identified as barriers to optimal pain management. Anon (2014), supports the findings on the importance of training in general and on cultural pain assessment and management in particular. Participants suggested that facility administrators create culturally appropriate pain guidelines.…”
Section: Discussionsupporting
confidence: 85%
“…The difficulties in identifying and assessing pain, as well as residents' resistance to reporting pain, were identified as barriers to optimal pain management. Anon (2014), supports the findings on the importance of training in general and on cultural pain assessment and management in particular. Participants suggested that facility administrators create culturally appropriate pain guidelines.…”
Section: Discussionsupporting
confidence: 85%
“…Drug treatment in aging subjects is a critical issue since a complex balance between adequate pain treatment without medication overuse and adverse effects is needed to enhance the quality of life and functions [ 22 ]. The use of opioid drugs, such as morphine for treating OA pain, is controversial, due to several reported side effects [ 49 , 50 , 51 , 52 ]. Studies with the MIA rodent model indicated that morphine efficaciously relieved pain-related behaviors acutely and in a short-term treatment [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain assessment starts from the first day of admission, and they mentioned various ways in which they conduct the assessment. According to Anon (2014), the health assessment must contain a complete medication history that includes current and old prescriptions and over-the-counter medications. Three categories emerged from the data: pain indicators, etiology of pain, and pain assessment tools.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment and measurement of pain in long-term care homes require a tool that is appropriately worded and easily understood (Flaherty, 2012). The Numeric Rating Scale is a widely used pain rating scale in long-term care homes (Anon, 2014).…”
Section: "I Use Behavioural Painmentioning
confidence: 99%